KESADARAN HUKUM WAJIB LAPOR KETENAGAKERJAAN PERUSAHAAN PADA YAYASAN PENDIDIKAN BERBASIS AGAMA ISLAM: STUDI KASUS KOTA SAMARINDA - Fadlurrahman , Muhammad Fais; Pratama, Rio Arif; Hasmiati , Rahmatullah Ayu (Gapenas Publisher, 2024)
Mandatory Company Employment Report (WLKP) has been regulated in Law No. 7 of 1981. According to the law, mandatory employment reporting is an obligation for all companies and employers who employ workers by paying wages or rewards, this obligation is for companies to carry out and report employment data to the local labor office, including the education sector, both educational foundations and other educational institutions, but in fact, there are still many educational institutions and educational foundations that are still not implement the provisions of the Company's Mandatory Employment Report. The purpose of this study is to find out how the Implementation of Mandatory Employment Reporting in the Education Sector, as well as what obstacles must be faced by various school foundations and obstacles faced by supervisors who are required to report to the company's employment. The method in this study uses an empirical juridical method, the data sources of this study are sourced from library research and Field Research. By the random sampling method. The results of the study show that there are still few educational foundations and educational institutions that have not implemented the provisions of the Mandatory Corporate Employment Report. It is recorded that only twenty (20) Foundations in East Kalimantan carry out the Mandatory Corporate Employment Report, from this data there are no foundations or educational institutions in Samarinda City. In this case, the lack of understanding of mandatory company employment report and the lack of supervisory resources are one of the main factors, and there are other obstacles that hinder the Mandatory Employment Reporting Process of Companies in the Education Sector